Rapid rural appraisal as research methodology in assessing impacts of community managed river diversions in Tanzania for the AgWater Solutions project - Gonsalves, Julian Francis (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2013)
Rapid rural appraisal was used in the first phase of the research, which covered 5 administrative regions in Tanzania (over 200 farmers from 10 irrigation schemes). The major finding was that investing in improvements to existing community-managed river diversion irrigation schemes can lead to gains in water productivity and household income. Infrastructure improvements, coupled with a watershed management approach, farmer training, micro-credit and marketing, can make a significant contribution to Tanzania’s poverty alleviation and development goals.